2019
DOI: 10.5194/tc-13-2557-2019
|View full text |Cite
|
Sign up to set email alerts
|

Mountain permafrost degradation documented through a network of permanent electrical resistivity tomography sites

Abstract: Abstract. Mountain permafrost is sensitive to climate change and is expected to gradually degrade in response to the ongoing atmospheric warming trend. Long-term monitoring of the permafrost thermal state is a key task, but problematic where temperatures are close to 0 ∘C because the energy exchange is then dominantly related to latent heat effects associated with phase change (ice–water), rather than ground warming or cooling. Consequently, it is difficult to detect significant spatio-temporal variations in g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 81 publications
(143 reference statements)
6
94
0
Order By: Relevance
“…The input data of the joint inversion problem consist of compressional wave travel times and apparent electrical resistivities. Apparent resistivity data were acquired through a Geotom instrument (Geolog, Germany) or a Syscal resistivity meter (Iris Instruments, France) and were filtered following the procedure described in Mollaret et al (2019). Seismograms were recorded through a Geode system (Geometrics, USA).…”
Section: Geophysical Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…The input data of the joint inversion problem consist of compressional wave travel times and apparent electrical resistivities. Apparent resistivity data were acquired through a Geotom instrument (Geolog, Germany) or a Syscal resistivity meter (Iris Instruments, France) and were filtered following the procedure described in Mollaret et al (2019). Seismograms were recorded through a Geode system (Geometrics, USA).…”
Section: Geophysical Datasetsmentioning
confidence: 99%
“…Annual geophysical measurements of the same profile are performed since 2013 (Pogliotti et al, 2015;Pellet et al, 2016;Mollaret et al, 2019). In the tomogram in Figure 2D, the lowest velocities (corresponding to a high air content) occurring in the near-surface are interpreted to be a porous debris layer.…”
Section: Cervinia Rock Plateaumentioning
confidence: 99%
See 1 more Smart Citation
“…Iterative tomographic inversions of apparent resistivities measured at different electrode locations and separations along a profile finally yield a two-dimensional model of the specific resistivity of the subsurface. The application of ERT has become a standard technique to image and monitor 220 variations of electrical resistivity in the near subsurface of mountain permafrost due to its sensitivity to the state of water (liquid or solid) in unfrozen and frozen conditions (Hauck, 2013;Hilbich et al, 2008;Mollaret et al, 2019).…”
Section: Electrical Resistivity Tomography (Ert)mentioning
confidence: 99%
“…ice-rich permafrost in rock glaciers are less sensitive to climatic warming than permafrost with low ice content (Scherler 55 et al, 2013) due to complex interactions of advective and convective heat fluxes and latent heat effects during freeze and thaw processes (Scherler et al, 2010). However, ice melt is also predicted for rock glaciers (Marmy et al, 2016) and already observed in the Alps (Mollaret et al, 2019).…”
Section: Introductionmentioning
confidence: 99%